A Study of Japanese University Students' Perceptions of Their Appearance and Their Tendency to Wear Masks During School During the COVID-19 - Nozomi, Komiya (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to shed light on the effects of COVID-19 on university students. Specifically, the author clarifies the habit of wearing masks, a characteristic among Japanese, and their self-perceptions regarding their appearance post-COVID. Methodology: The author hypothesizes that students who have not had the opportunity to see the real faces of their classmates since entering university will have great resistance to removing their masks in public. The hypothesis will be tested and analyzed by conducting a questionnaire survey of 357 students in Japan to investigate their perceptions of their faces during FY2023. Main Findings: As of May 2023, 357 students (191 males and 166 females) in Japanese universities underwent Cross tabulation and Chi-Square analysis to examine shifts in their attitudes toward appearance and mask-wearing habits. The study revealed significant differences in attitudes and mask-wearing tendencies between the two genders (p < .001, p = 7.6E-07, = 24.5). Novelty/Originality of this study: It has been discovered through this study that a greater number of female students continue to wear masks even when it is no longer mandated. This difference in behavior between genders is statistically significant, confirming the hypothesis. The survey also uncovered the reasons behind this behavior, including habituation, changes in self-perception, and the influence of the surrounding.